Update on Babesiosis - Edouard Vannier; Peter J. Krause (Interdisciplinary Perspectives on Infectious Diseases)
Human babesiosis is an emerging tick-borne infectious disease caused by intraerythrocytic protozoan species of the genus Babesia with many clinical features similar to those of malaria. Over the last 50 years, the epidemiology of human babesiosis has changed from a few isolated cases to the establishment of endemic areas in the northeastern and midwestern United States. Episodic cases are reported in Europe, Asia, Africa, and South America. The severity of infection ranges from asymptomatic infection to fulminant disease resulting in death, although the majority of healthy adults experience a mild-to-moderate illness. People over the age of 50 years and immunocompromised individuals are at the highest risk of severe disease, including those with malignancy, HIV, lacking a spleen, or receiving immunosuppressive drugs. Asymptomatic carriers present a blood safety risk when they donate blood. Definitive diagnosis of babesial infection generally is made by microscopic identification of the organism on thin blood smear, amplification of Babesia DNA using PCR, and detection of Babesia antibody in acute and convalescent sera. Specific antimicrobial therapy consists of atovaquone and azithromycin or clindamycin and quinine. Exchange transfusion is used in severe cases. The use of multiple prevention strategies is recommended and consists of personal, residential, and community approaches.